A Case of Two Abdominal Gossypibomas in a Patient: A Rare Case Report - Batra, Radhika; Gautam, Richa; Manchanda, Alpana; Ghuliani, Deepak (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Gossypiboma is a rare condition caused by retention of a foreign body, most commonly surgical sponge following any surgical procedure. The patient may be asymptomatic, can present with vague symptoms, or rarely with acute symptoms depending on the location of the foreign body and the complications associated with it; thus it may be difficult to diagnose this condition. A 30-year-old woman presented to our hospital with complaints of lump and mild pain on both sides of the lower abdomen for 3 months following caesarean section which was performed in a rural hospital. Ultrasound and computed tomography findings along with the classical history helped in arriving at the diagnosis of two gossypibomas in lower abdomen, one in each flank which was further confirmed on laparotomy.
Keywords: abdomen; foreign body; gossypiboma; retained surgical items